AB0462 The Risk of Cancer in Systemic Lupus Erythematosus in Chinese Population: A Single-Center Experience. (15th July 2016) - Qi, J.; Zhang, P.; Hu, Z.; Chen, Z.; Gu, J.
Abstract : Background: It was reported that incidence rate of malignant tumor in general population was 0.24% in China in 2010. Cyclophosphamide is widely used in the treatment of systemic lupus erythematosus. Long term use of CTX may lead to increase the risk of tumor. However, whether the Cyclophosphamide risk of cancer will increase is not clear. Objectives: To investigate the risk of cancer in systemic lupus erythematosus patients. Methods: We studied retrospectively systemic lupus erythematosus patients coexist with malignancies hospitalized in the Third Affiliated hospital of Sun Yat-sen University from 1999 to 2015. The study included 2530 systemic lupus erythematosus patients. Results: The ratio of systemic lupus erythematosus with malignancies was 0.24% in these patients (6/2530). Compared to general population, no increase in tumor incidence was found in systemic lupus erythematosus. The onset age of SLE was 47±17.8years, and the age of the patients with cancer were 50.7±14.9years.There were 6 solid tumor in our study, including three thyroid carcinoma, one nasopharyngeal carcinoma, one nerve glioma, and one meningioma. Conclusions: The incidence of tumor in SLE patients was similar to the general populations. References: Chen, W.; Zheng, R.; Zhang, S.; Zhao, P.; Zeng, H.; Zou, X., Report of cancer incidence and mortality in China, 2010. Annals of translational medicine 2014, 2 (7), 61. Disclosure of Interest: None declared